Management of Anesthesia in Laparoscopic Cholecystectomy During First Trimester Pregnancy - Sudiantara, Putu Herdita; Juwita, Nova; Ariyasa EM, Tjahya; Senapathi, Tjok Gede Agung (Majalah Anestesia & Critical Care, 2023)
Pregnant women increase the risk of gallbladder disease. Acute cholecystitis occurs 1-6 per 10.000 pregnancy and Cholecystectomy is the second most frequent procedure in pregnancy. Biliary stasis and biliary smooth muscle relaxation due to elevated estrogen and progesterone hormones during pregnancy can lead to gallstones formation. Cholelithiasis complications associated with choledocholithiasis, acute cholecystitis, cholangitis and, gallstone pancreatitis that posing significant morbidity and mortality like spontaneous abortion, preterm labor, and fetal loss. Laparoscopic surgical techniques are no longer a contraindication to non-obstetric surgery for pregnant women although they still have a risk of developing fetal development disorders. Management of anesthesia in laparoscopic cholecystectomy during pregnancy must consider the risk of anesthesia surgery, from the disease, maternal and fetal condition, and manipulation when surgeon performing laparoscopic. This report presenting a 33-years-old woman with 10-week pregnancy who undergoes laparoscopic cholecystectomy followed by symptomatic cholelithiases. It was done with general anesthesia combined with epidural analgesia. After the procedure, there is no complaint about abdominal pain or vaginal bleeding. The patient was discharged 3 days aftercare.